An antenatal wish list: A qualitative systematic review and thematic synthesis of UK dietary advice for weight management and food borne illness. (March 2020) - Stockton, Jessica; Nield, Lucie
Abstract: Objectives: To understand UK women's experiences of antenatal dietary advice for risk of food borne illness and weight gain. Design: A systematic review and thematic synthesis of peer-reviewed qualitative studies. PubMed, MEDLINE, CINAHL and PMC databases were searched for articles published from January 2008 to June 2018. The search strategy combined terms for pregnancy with terms for body composition, weight change, food safety, nutrition, diet and qualitative terminology. Studies were eligible for inclusion if (1) they explored experiences of implementing advice received during pregnancy for nutrition, physical activity and/or weight gain, and (2) participants were women who had experienced maternity care in the UK. Study quality was appraised using the Critical Appraisal Skills Programme (CASP) qualitative research appraisal tool. Findings: Of 25, 688 articles identified by the search strategy, 20 studies were identified that met the inclusion criteria. Five major themes were recognised: control, barriers to diet and exercise, motivators, relationship with weight, and information, with a further 12 subthemes. The majority of studies reported on weight gain ( n  = 10). Key conclusions: Evidence shows that UK antenatal dietary advice is currently inconsistent, vague and overwhelming despite pregnancy being an excellent time for lifestyle change. Women are primarily driven by the health of their baby and desire support to facilitate positive changes. Implications for practice: Findings outline a wishlist which highlights a desire for tailored information on preventing weight gain, dietary requirements, safe physical activity and a deprioritisation of food safety guidelines. This provision should be delivered by HCP. e.g. midwives, in a sensitive and supportive way to bridge the gap between women's needs and the current antenatal provision.